Evaluación del potencial energético de la línea de conducción para agua potable Presa Chiquihurco - Planta de Tratamiento Apatug 2013. Diseño de un sistema para el aprovechamiento de la energía hidráulica. - Arteaga López, Oscar Bladimir (2015)
This paper evaluates the energy potential of the pipeline for water supply Chiquihurco Dam - Apatug Treatment Plant in the province of Tungurahua, this study is based on the theoretical foundation and hydrological, topographical and geotechnical studies developed in the area. In this study the design of a small hydroelectric plant is proposed, which shows the advantages of: harnessing the raw water flow provided to Empresa Pública – Empresa Municipal de Agua Potable y Alcantarillado de Ambato (EP-EMAPA-A), using the particular topographic and soil conditions where the pipeline that transports such water to the treatment plant cuts across, and ensuring the maximum possible power generation and continuity in the by-gravity water supply to the treatment plant, even in situations where it is necessary to stop the operation of the turbine for maintenance or contingencies. The profitability of the proposed alternative is determined by the results analysis. The plant designed is capable of generating 1,08 MW with an acceptable investment of $ 1 927 650.79 and little environmental impact as several of the works developed for the Chiquihurco High Zone in Ambato water supply system can be used and with less environmental impact than that produced by other sources of electricity generation such as oil, solar and wind.